Organizing for Mass Customization: Literature Review and Research Agenda - Sandrin, Enrico; Trentin, Alessio; Forza, Cipriano (International Journal of Industrial Engineering and Management, 2014)
Due to the increase in sophisticated customer needs and intense competition, mass customisation has increasingly drawn the attention of companies and scholars. The importance of transforming organisations by building mass customisation capability has long been acknowledged. However, the discussion is generally scattered and disorganised in the literature. This paper reviews the mass customisation literature with the twofold purpose of providing a comprehensive and structured overview of prior research on mass customisation organisational antecedents and highlighting future opportunities to research this topic. By using an established framework in the organisation design theory, the paper provides comprehensive coverage of organisation-related issues and a reference for future research opportunities. Article history: Received (27.07.2014); Revised (20.11.2014); Accepted (02.12.2014)